Macrozoobenthos of small lowland lakes of Sakhalin Island - Vyacheslav S. Labay (Известия ТИНРО, 2015)
Species composition, structure and seasonal dynamics of macrozoobenthos in small lakes of Sakhalin Island are considered on the data of benthic surveys conducted in 1994-2012. Features of the bottom fauna are determined by the lakes origin, their connection with other water bodies, biotic and abiotic conditions. The faunas of the lakes of northern Sakhalin are distinguished by the highest similarity. Generally, variety of benthic communities in small lakes corresponds to their biotope diversity and reduces with the size of lakes decreasing. The most typical benthic communities are those ones of the coastal belt of rigid plants, of the belt of pondweed, and profundal community of the open water area; the latter only is observed in very small lakes. Seasonal dynamics of the benthic communities is defined by biology of a few key species which dominate the whole year round. For example, seasonal dynamics of the profundal community in small floodplain lakes is determined mainly by generative dynamics of one species of chironomid: Chironomus gr. plumosus . Three phases could be traced in the seasonal succession: i) winter; ii) spring and early summer; iii) late summer and autumn. They change under influence of seasonal events as spring flood, summer low water, ice formation, or mass fish migration (reaction of benthic communities on fish migration is adaptive, not catastrophic). Food web of the benthic communities in small lakes is based on autochthonous organic matter of phytoperiphyton, phytobenthos and phytoplankton settled to the bottom. Benthic communities of floodplain lakes play important role in preserving of rheophilic fauna during catastrophic floods.